2016
DOI: 10.1016/j.molimm.2016.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine-induced modulation of gene expression in turbot peritoneal cells. A microarray approach

Abstract: We used a microarray approach to examine changes in gene expression in turbot peritoneal cells after injection of the fish with vaccines containing the ciliate parasite Philasterides dicentrarchi as antigen and one of the following adjuvants: chitosan-PVMMA microspheres, Freund́s complete adjuvant, aluminium hydroxide gel or Matrix-Q (Isconova, Sweden). We identified 374 genes that were differentially expressed in all groups of fish. Forty-two genes related to tight junctions and focal adhesions and/or actin c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 61 publications
(78 reference statements)
0
6
0
Order By: Relevance
“…Previous studies have shown that P. dicentrarchi proteases induce apoptosis in turbot cells [ 14 ]. However, increased expression of genes related to apoptosis or in the number of apoptotic cells in turbot peritoneal cells after injection with other stimuli have also been observed [ 31 , 78 ]. Other studies have also shown that large numbers of neutrophils migrate to the peritoneal cavity after injection of P. dicentrarchi [ 21 ] and many of these cells seem to initiate the expression of genes leading to apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that P. dicentrarchi proteases induce apoptosis in turbot cells [ 14 ]. However, increased expression of genes related to apoptosis or in the number of apoptotic cells in turbot peritoneal cells after injection with other stimuli have also been observed [ 31 , 78 ]. Other studies have also shown that large numbers of neutrophils migrate to the peritoneal cavity after injection of P. dicentrarchi [ 21 ] and many of these cells seem to initiate the expression of genes leading to apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Ef1 -α was identified as the most stable in both cases and was therefore selected as the reference gene for qPCR analysis. The qPCR analysis was carried out as previously described [ 31 ]. Relative gene expression was quantified by the 2 −ΔΔC t method [ 32 ] applied with software conforming to minimum information for publication of qRT-PCR experiments (MIQE) guidelines [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, MHC I plays an important role in host immunity mechanisms against intracellular bacterial pathogens (Buttrum et al, ), such as V. harveyi (Wang et al, ). The low expression of CCL4 in the gill following bath vaccination with LAVh and FKVh could be related to the low population of lymphocytes in gills (Fontenla et al, ). But the high expression of CCL4 in the liver, kidney and skin at 24 hr post‐vaccination indicates the capability of LAVh to induce innate immune response in internal organs as well as in mucosal organs, such as the skin.…”
Section: Discussionmentioning
confidence: 99%
“…), acute phase protein genes (SAA, SAP1 and COX-2), antimicrobial peptide genes (CATH1, CATH2 and LEAP1), as well as adaptive cytokine genes (IFNγ, IL-17A/F and IL-4/13) are increased in PBL by bacterin vaccine candidates in this study. Their expression is also increased in vivo by injection vaccination in rainbow trout [18,30,61], Atlantic salmon [33,62] and other fish species [63][64][65].…”
Section: Pbl Immune Gene Expression Mimics the In Vivo Response To Vamentioning
confidence: 99%
“…Consequently, immune gene expression in response to vaccination can be different in different tissues [29,30,65], and can even show fish species-specificity [66]. For example, genes associated with T and B lymphocyte activity and migration, such as CCR7 and CCR9, are decreased in peritoneal cells after intraperitoneal injection vaccination [63]. This decreased gene expression may be a consequence of different phenomena, that include a rapid influx of myeloid cells to the peritoneal cavity after vaccination [67], or exit of leucocytes expressing high levels of CCR7 and CCR9 that home to secondary lymphoid tissues to initiate adaptive immune responses, or the actions of both.…”
Section: Pbl Immune Gene Expression Mimics the In Vivo Response To Vamentioning
confidence: 99%